2021
DOI: 10.3390/jcm10132936
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Multicenter Study of “Inside Stents” for Biliary Stricture: Multicenter Evolving Inside Stent Registry (MEISteR)

Abstract: Background: Endoscopic biliary stent placement is the standard of care for biliary strictures, but stents across the papilla are prone to duodenobiliary reflux, which can cause stent occlusion. Preliminary studies of “inside stents” placed above the papilla showed encouraging outcomes, but prospective data with a large cohort were not reported. Methods: This was a prospective multicenter registry of commercially available inside stents for benign and malignant biliary strictures. Primary endpoint was recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
(36 reference statements)
2
8
0
Order By: Relevance
“…[7][8][9][10]13,14 In addition, a multicenter prospective study showed that TRBO for malignant biliary stricture was 4.7 months. 15 Thus, our results regarding TRBO in the IS group were comparable with those of most previous studies. However, the reason why the median TRBO with ISs (113 days, or 3.7 months) in this study was slightly shorter than the results of a previous prospective study (4.7 months) might be explained by aggressive IS exchange when cholangitis occurred, even in patients who had non-occlusion cholangitis without obvious jaundice (total bilirubin < 2.0 mg/dl).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[7][8][9][10]13,14 In addition, a multicenter prospective study showed that TRBO for malignant biliary stricture was 4.7 months. 15 Thus, our results regarding TRBO in the IS group were comparable with those of most previous studies. However, the reason why the median TRBO with ISs (113 days, or 3.7 months) in this study was slightly shorter than the results of a previous prospective study (4.7 months) might be explained by aggressive IS exchange when cholangitis occurred, even in patients who had non-occlusion cholangitis without obvious jaundice (total bilirubin < 2.0 mg/dl).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies had found that IS patency in malignant biliary obstruction ranged from 85.2 to 190 days 7–10,13,14 . In addition, a multicenter prospective study showed that TRBO for malignant biliary stricture was 4.7 months 15 . Thus, our results regarding TRBO in the IS group were comparable with those of most previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…A slim-covered SEMS (6 mm diameter) and a stent placed above the papilla show promise for unresectable hilar MBO because of their long TRBO and exchangeability (Figs 2,3). 18 MANAGEMENT OF BENIGN BILIARY STRICTURE B ENIGN BILIARY STRICTURE (BBS) can be treated with CSEMS instead of PS. CSEMS placement for BBS was first reported in Japan in 2003 by Enya et al, 19 who used the polyurethane-covered Strecker stent and Diamond stent.…”
Section: Management Of Hilar Mbomentioning
confidence: 99%
“…A slim‐covered SEMS (6 mm diameter) and a stent placed above the papilla show promise for unresectable hilar MBO because of their long TRBO and exchangeability (Figs 2,3). 18 …”
Section: Management Of Hilar Mbomentioning
confidence: 99%
“…This stent was developed by a Japanese endoscopist [12][13][14] but has not been evaluated prospectively or in a comparative study. A prospective single-arm multicenter study evaluated the feasibility of an inside stent [15]. The inside stent showed a long time to RBO in cases of benign biliary stricture (BBS) and superiority to conventional plastic stents in malignant cases.…”
mentioning
confidence: 99%